(untitled) (Innovare: Revista de ciencia y tecnología, 2021)
On January 2021, a 62-year-old woman complained of “allergy” in her forearm. She had taken generic ivermectin (IVM) 6mg per week as COVID-19 prophylaxis for two weeks before the eruption. She stopped the medication and improved, but symptoms reactivated after IVM was restarted (A). On examination, there was a 4 cm diameter erythematous violaceous plaque. There was improvement after treatment with oral prednisolone and topical betamethasone (B & C). The patient had presented paracetamol-related eruption in her tongue some years before. Physicians should be aware of ivermectin-induced fixed drug eruption, since this drug is being widely used during the COVID-19 pandemic.